Clinical evidence for elevated levels of caveolin‐1 in circulation of patients with diabetic foot ulcers. Issue 1 (30th November 2021) - Sheng, Qizhi; Li, Guanglei; Liu, Huimin; Liu, Ping
Abstract: Caveolin‐1 directly interacts vascular endothelial growth factor receptor‐2 (VEGFR2) and therefore prevents VEGF‐induced angiogenesis. In addition, the production of nitric oxide (NO), which is effective in reducing ischemia in diabetic foot ulcers (DFU), is suppressed by caveolin‐1 in endothelial cells. The present study was designed to investigate the change of caveolin‐1 concentrations in DFU patients. A total of 150 participants were consecutively enrolled, including 40 DFU patients (DFU group), 40 diabetes patients without DFU (type 2 diabetes mellitus [T2DM] group), and 70 participants without diabetes (control group). Significant increased levels of plasma caveolin‐1, accompanied with decreased concentration of plasma VEGF‐A (vascular endothelial growth factor‐A) and NO, were detected in DFU patients. Moreover, Pearson's correlation analysis revealed a negative correlation between plasma caveolin‐1 and VEGF‐A as well as NO levels in DFU patients. Furthermore, DFU patients had higher expression of caveolin‐1 in the popliteal artery, compared to those in control and T2DM groups. Simultaneously, the amounts of eNOS (an enzyme responsible for the production of NO) and VEGFR2 were attenuated in the popliteal artery of DFU patients. Taken together, our study provided clinical evidence for the possible association of elevated caveolin‐1 levels and the development of DFU. This may be induced by the suppressed VEGF‐A/VEGFR2 and eNOS/NO signalling axis.